2018
DOI: 10.7494/geol.2018.44.4.345
|View full text |Cite
|
Sign up to set email alerts
|

The effect of waste sulfur obtained during biogas desulfurization on the availability of selected trace elements in soil

Abstract: Research concerning the effect of the application of waste sulfur pulp (doses: 10, 20, 30, 60 mg S · kg -1 d.m. of soil) on selected soil properties was carried out. The pulp contained sulfur in the elemental form. Before setting up the experiment, the soil had a slightly acid reaction (determination in 1 mol · dm -3 KCl) and was not contaminated with heavy metals. After conducting the incubation experiment, it was observed that the application of sulfur pulp led to a statistically significant (and proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The decrease in the soil pH intensified over time, which was in line with the results shown in the studies of Krzebietke and Benedycka [19] and Ochmian et al [33]. Fertilization can directly or indirectly change the soil's chemical, physical, and microbiological properties, thereby influencing its productivity [34,35].…”
Section: Soil Phsupporting
confidence: 82%
“…The decrease in the soil pH intensified over time, which was in line with the results shown in the studies of Krzebietke and Benedycka [19] and Ochmian et al [33]. Fertilization can directly or indirectly change the soil's chemical, physical, and microbiological properties, thereby influencing its productivity [34,35].…”
Section: Soil Phsupporting
confidence: 82%
“…Heavy soil abundance after sulfur application was at least medium (the highest after application of the double dose of sulfur and ground phosphate rock -anthropogenically elevated). An increase in soil abundance in sulfate sulfur after application of elemental sulfur has been recorded earlier (Bobowiec and Tabak, 2018;Kulczycki, 2015;Stanisławska-Glubiak et al, 2012). Intensity of elemental sulfur oxidation depends on temperature, moisture and pH of soil (optimum: 20-30ºC, moisture approximately 60%, pH 6.0-7.0) (Hoffman et al, 2014), activity of oxidizing bacteria (Acidithiobacillus thiooxidans), and also on properties of sulfur material (including the size of particles, which determines the degree of contact with soil).…”
Section: Figure 1 Soil Ph Kcl During the Incubationmentioning
confidence: 66%
“…Previous studies confirmed soil acidification after sulfur application (Bobowiec and Tabak, 2018;Kulczycki, 2015;Yang et al, 2010). Such acidification can be limited by liming; adjustment of the soil reaction is also beneficial for the activity of sulfur oxidizing microorganisms (Bobowiec and Tabak, 2018).…”
Section: Figure 1 Soil Ph Kcl During the Incubationmentioning
confidence: 93%
See 2 more Smart Citations